Atherosklerosis and dementia - Zatloukalová, Anna; Roubec, Martin; Školoudík, David; Ambroz, Petr; Machaczka, Ondřej; Janoutová, Jana; Janout, Vladimír (Profese Online, 2020)
Background: The number of patients with atherosclerosis and dementia is increasing, mainly due to the increase in life expectancy and population aging. Both diseases are closely related and at the same time significantly affect the quality of life of patients. Objective: The aim of this communication is to present this topical issue across the field of expertise. Methods: Data were taken from current publications, especially from PubMed database. Furthermore, other databases and results of clinical trials were used, both foreign and Czech. Results: Research suggests that atherosclerotic involvement of carotid arteries is a potential predictor of the risk of developing dementia. The manifestations of carotid atherosclerosis are associated with cognitive deficits and dementia. Identified risk factors for atherosclerosis often occur in patients with dementia. It can therefore be concluded that they are closely linked. Conclusions: Life expectancy is likely to continue to increase, so the number of patients with this disease will increase. That is why epidemiological research is needed to address this issue. Based on the research, effective prevention, diagnosis and treatment of these conditions can be formulated.
Keywords: atherosklerosis; dementia; Alzheimer's disease; risk factors; prevention